Retrospective record based study of maternal and fetal outcome in induction of labour at 40 and 41 weeks of gestation in uncomplicated primigravida women - Anand, Mamta N.; Ubale, Sunita M.; Anand, Neelesh P.; Naykodi, Priti; Senapati, Jaynarayan B.; Babalgaonkar, Anjali A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The objective of the study was to compare maternal and foetal outcome after induction in two groups: women who were induced at 40-weeks and at 41-weeks. Methods: This was a retrospective study conducted over period of one year from 1 January 2018 to 31 December 2018 in the obstetrics and gynaecology department. A total of 200 uncomplicated primigravida women were included in the study. The data was collected and comparative analysis was done between two groups: control group (group A), women with induction at 40 weeks; study group (group B), women with induction at 41 weeks. The outcome was then analysed in terms of mode of delivery, oligohydramnios, meconium-stained liquor, Apgar score, need of NICU, perinatal death. The data was collected, analysed and statistical analysis was done using the Chi square test. Results: Out of total 200 women, 104 women were of 40 weeks and 96 women had completed 41 weeks. The LSCS rate was reduced from 25.96% to 17.7%, when the labour was induced at 41 weeks, the instrumental delivery rate was low in the study group compared to the control group. Even though the meconium staining of liquor was high but NICU admission and perinatal mortality was comparatively lower in the study group. Conclusions: Induction of labour done at 41weeks is associated with reduced maternal morbidity and no adverse effect on the perinatal outcome as compare to induction at 40 weeks.